Targeting the Immune System to Fight Cancer Using Chemical Receptor Homing Vectors Carrying Polyinosine/Cytosine (PolyIC) - Levitzki, Alexander (Frontiers in Oncology, 2012)
Cancer researchers have been looking for ways to harness the immune system and to reinstate immune surveillance, to kill cancer cells without collateral damage. Here we scan current approaches to targeting the immune system against cancer, and emphasize our own approach. We are using chemical vectors attached to a specific ligand, to introduce synthetic dsRNA, poly Inosine/Cytosine (polyIC), into tumors. The ligand binds to a receptor protein that is overexpressed on the surface of the tumor cells. Upon ligand binding, the receptor complex is internalized, introducing the polyIC into the cell. In this fashion a large amount of synthetic dsRNA can be internalized, leading to the activation of dsRNA binding proteins, such as dsRNA dependent protein kinase (PKR), Toll-3 receptor (TLR3), retinoic acid–inducible gene I (RIG-1) and melanoma differentiation–associated gene 5 (MDA5). The simultaneous activation of these signaling proteins leads to the rapid demise of the targeted cell and to cytokine secretion. The cytokines lead to a strong bystander effect and to the recruitment of immune cells that converge upon the targeted cells. The bystander effects lead to the destruction of neighboring tumor cells not targeted themselves by the vector. Normal cells, being more robust than tumor cells, survive. This strategy has several advantages: (1) Recruitment of the immune system is localized to the tumor. (2) The response is rapid, leading to fast tumor eradication. (3) The bystander effects lead to the eradication of tumor cells not harboring the target. (4) The multiplicity of pro-death signaling pathways elicited by PolyIC minimizes the likelihood of the emergence of resistance. In this chapter we focus on EGFR as the targeted receptor, which is overexpressed in many tumors. In principle, the strategy can be extended to other tumors that overexpress a protein that can be internalized by a ligand, which be a small molecule, a single chain antibody or an affibody.